Hi-Tech Smart Shoe Rack / Mohd Danial Arieff Mohd Ghafoor … [et al.] - MOHD GHAFOOR, MOHD DANIAL ARIEFF; ISMAIL, PUTERI NADHIRAH; MOHD SHUKRI, SYARIZAD SOFIA; RAHMAN, FATHIIN NABIILAH; NOR WAHID, FARRAH KHALIDAH (2018)
SmartTech Corp is company venturing new products and innovation to enhance overall lifestyle of the current and future generation. The team produced smart shoe rack to replace current shoe rack in the market. This smart shoe rack is equipped with modern high technology such as auto pickup, QR scanner and alarm system. This product is believed to solve problems in every store room with current technology rack..